ENT530: Business plan Decor and Decor Furniture / Nuraqila Zulkifli, Musliza Munirah Che Musa and Nur Ain Mohamed Abdul Fatah - Zulkifli, Nuraqila; Che Musa, Musliza Munirah; Mohamed Abdul Fatah, Nur Ain (2017)
We chose this business because it will generate profit besides furniture can be innovated with different kind of shapes and it will attract customer to purchase our products as we also offer affordable prices. New design and innovated of furniture which different from others. Then the demand of the furniture will increase due preparing new, unique and innovative product. Supply high quality of furniture that will be more flexible.